Investigating the compliance of signage boards for two-storey shop lots in Pekan Mentakab, Pahang Darul Makmur / Puteri Izyan Izzaira Mohd Ridzuan and Jamaludin Muhamad - Mohd Ridzuan, Puteri Izyan Izzaira; Muhamad, Jamaludin (2023)
This aims to evaluate the compliance of signage boards on two-storey building facades in Pekan Mentakab. In Mentakab town, signage boards are commonly used for communication and shop identification. However, inappropriate signage board design can deface the appearance of the building's facade. Ideally, signage boards should integrate harmoniously with the overall architectural design rather than stand out as separate elements. Surprisingly, there seem to be no existing guidelines for installing signage boards on buildings. Therefore, this study seeks to identify the guidelines provided by local authorities for signage board installations on business shop lot buildings and examine the enforcement of these guidelines in Mentakab town. The focus will be on shop lot buildings located on Jalan Mok Hee Kiang, Mentakab. The research methodology involves extensive observation, photo collection, and various studies to gather and analyze relevant data. The findings indicate that the majority of business shop lot owners show little concern for proper signage boards, as well as the safety and comfort of both building occupants and passersby. This highlights the importance of adhering to signage board guidelines to preserve the aesthetic appeal of building facades and ensure public safety and comfort. Despite being a seemingly small component, signage boards have a significant impact on the building and its environment.